CARACTERIZAÇÃO DA POPULAÇÃO COM CONSUMOS DE ÁLCOOL DO NORTE DE PORTUGAL: ANÁLISE DE DADOS DO MUNDO REAL - Manuela Cristiana Oliveira Araújo (2022)
Alcohol Related Problems (APL) are an important global health problem, with implications in various aspects of individual's life's. The reasons that should drive investment in health policies and the adoption of organizational strategies oriented towards the prevention and treatment of APL are mainly three: the high prevalence of APL, the high associated morbidity and mortality and the high health costs that excessive consumption of alcohol entails. Portugal ranks 11th on the WHO list of European countries with the highest total per capita alcohol consumption (12.3 liters of pure alcohol). For the Portuguese population, alcohol and drug consumption are among the risk factors that most contribute to the total number of years of healthy life lost (DALY), totalizing 8.7% of the disease burden. In terms of mortality, according to the National Institute of Statistics, in 2018 there were 2493 deaths from alcohol-related diseases in Portugal. The high consumption of alcoholic beverages is a relevant risk factor for a significant number of diseases. The occurrence of a significant number of road accidents, violence, homicides and suicides is also frequently attributed to the excessive consumption of alcohol, especially among younger people. Given the high prevalence of excessive alcohol consumption and the problems related to it, it is opportune to carry out studies that characterize the profile of the population with alcohol consumption. Objectives: Determine the prevalence, at 31.12.2020, of chronic alcohol abuse in the ARSN population, based on the coding performed by family doctors: ICPC-2 of P15-Chronic Alcohol Abuse coding. Characterize and interpret the profile of the population with alcohol consumption in the ARSN. Estimate the use of the Audit-C/Audit brief intervention tool. Methodology: Study Type: Retrospective and analytical longitudinal observational study. Population of the study: Patients with ICPC-2 coding of P15-Chronic Alcohol Abuse, enrolled in the lists of patients of the ARSN Healthcare Units, aged 18 years or over. Information source: Data recorded in SIARS (ARS Information System) in patients with the ICPC-2 coding of P15-Chronic Alcohol Abuse, in the ARSN. Statistic analysis: The software to be used for data processing will be Microsoft Office Excel 2016® and SPSS Statistics 27.0®.